Development of a novel diagnostic assay for insulin receptor autoantibodies based on a patient with autoimmune hypoglycaemia - Geng, Leiluo; Wong, Cheuk-Lik; Liao, Boya; Lin, Ying; Han, Hao; Lam, Karen S. L.; Xu, Aimin; Lee, Chi-Ho; Tam, Vicki H. K. (Frontiers in Endocrinology, 2022)
Differential diagnosis of hypoglycaemia can at times be challenging for patients who appear to be well. Here we identify the case of a 66-year-old Chinese man presenting with recurrent episodes of fasting hypoglycaemia and confusion without any other manifestations. He had no personal or family history of diabetes, nor was he on any hypoglycaemic drugs. The fasting insulin levels were elevated while the C-peptide and pro-insulin levels were slightly low or normal. Antibodies against insulin were negative and levels of insulin-like growth factors were normal. A series of imaging diagnosis excluded the presence of insulinoma or ectopic insulin-secreting neuroendocrine tumor. Ultimately, insulin receptor autoantibodies (IRAb) were detected by both immunoprecipitation assay and enzyme-linked immunosorbent assay (ELISA) developed in house. In a cell study, the immunoglobulins isolated from this patient exerted insulin-like effects on stimulation of post-insulin receptor signaling and glucose uptake as well as inhibited 125I-insulin binding with insulin receptors. Collectively, this patient was diagnosed with IRAb-induced autoimmune hypoglycaemia. Although this patient had no obvious immune disorders, several autoantibodies were identified in his plasma samples, suggesting the patient might have mild aberrant autoimmunity and therefore generated IRAb. IRAb-related disease is uncommon and possibly underdiagnosed or missed due to the lack of simple detection methods for IRAb. Our in-house user-friendly ELISA kit provides a valuable tool for diagnosis of this disease.